2016
DOI: 10.4236/oje.2016.61004
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution in the Gulf of Mexico

Abstract: An integral analysis of Air Pollution in the Gulf of Mexico was made considering pollutants emissions assessment and diagnosis; air pollution monitoring; and modeling of air pollution dispersion. Combustion sources considered in this work were: thermoelectric power plants and open flares; and pollutants considered were sulfur dioxide, nitrogen dioxides, particulate matter (PM 10 and PM 2.5 ), Total suspended particles (TSP) and carbon monoxide (CO). This study made evident a lack of more recent information and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Activity metrics and locations of oil and gas sector emission sources were available through the mining of data from Mexico's federal agencies and cooperative international initiatives, but emission factors in this and prior studies have been drawn from U.S. resources, including the EPA and BOEM. In assessments of earlier bottom-up inventories, Muriel-García et al [38] noted the needs for emission measurements and the homogenization of emission factors. Zavala-Ariaza et al [66] suggested the main driver for inaccuracies in the Mexican greenhouse gas inventory to be the use of emission factors that are not specific to Mexico.…”
Section: Improving Contemporary Inventoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Activity metrics and locations of oil and gas sector emission sources were available through the mining of data from Mexico's federal agencies and cooperative international initiatives, but emission factors in this and prior studies have been drawn from U.S. resources, including the EPA and BOEM. In assessments of earlier bottom-up inventories, Muriel-García et al [38] noted the needs for emission measurements and the homogenization of emission factors. Zavala-Ariaza et al [66] suggested the main driver for inaccuracies in the Mexican greenhouse gas inventory to be the use of emission factors that are not specific to Mexico.…”
Section: Improving Contemporary Inventoriesmentioning
confidence: 99%
“…This study developed a bottom-up emissions inventory for VOCs, NO x , SO 2 , CO, and fine particulate matter (PM 2.5 ) from upstream and midstream sector sources, including onshore and offshore well sites, gas flaring, natural gas processing facilities, and natural gas compressor stations for the 2016 base year across Mexican basins as a foundation for assessing future national policies and oil and gas production activity. We found previous bottom-up emissions estimates of these pollutants in Mexico within the public domain to be limited and to differ in spatial coverage, emission sources, and temporal resolution [34][35][36][37][38]. Earlier inventories have also represented time periods with different oil and gas production volumes in Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…This area is very important to consider, since the level of industrial sector activity is very interesting to evaluate (Muriel-García et al [9]).…”
Section: Introductionmentioning
confidence: 99%
“…Such influence may well explain why the main aquatic ecosystems within the state are wracked by industrial discharges, and why the Seco River, a major waterway, is troubled by a large concentration of physico-chemical and biological pollution (Ferrer-Sánchez et al, 2014). Tabasco is also bedeviled by persistent air pollution, but information about air quality is not made public, and an air quality monitoring system around the Paraiso, Tabasco, municipality is no longer functional (Muriel-García, Cerón-Bretón, & Cerón-Bretón, 2016). It does not appear as though the state has a dedicated office set aside for combating air pollution issues.…”
Section: Tabascomentioning
confidence: 99%